Disordered mesoporous carbon activated peroxydisulfate pretreatment facilitates disintegration of extracellular polymeric substances and anaerobic bioconversion of waste activated sludge. (November 2021) - Zhang, Ruiliang; Lu, Xueqin; Tan, Yujie; Cai, Teng; Han, Yule; Kudisi, Dilibaierkezi; Niu, Chengxin; Zhang, Zhongyi; Li, Wanjiang; Zhen, Guangyin
Graphical abstract: Highlights: DMC-activated PDS oxidation was used to pretreat sludge. Pretreatment promoted the dissolution of intracellular polymers. Methane productivity was notably enhanced by pretreatment. Modified Gompertz model was used to simulate biodegradation kinetics. Abstract: The potential of disordered mesoporous carbon (DMC) as catalyst of peroxydisulfate (PDS) to improve sludge solubilization and methane production was investigated. Results showed that DMC activated PDS (DMC/PDS) to produce sulfate radicals (SO4 − ), facilitating cells rupture and sludge matrix dissociation by degrading the carbonyl and amide groups in organic biopolymers (especially proteins, polysaccharides and humus). At the optimal DMC/PDS dosage of 0.04/1.2 g-mmol/g-VS, SCOD was increased from initial 294.0 to 681.5 mg/L, with the methane production rate of 12.6 mL/g-VS/day. Moreover, DMC could serve as electron mediator to accelerate electron transfer of microorganisms, building a more robust anaerobic metabolic environment. Modelling analysis further demonstrated the crucial role of DMC/PDS pretreatment in biological degradation and methane productivity. This study indicated that DMC/PDS pretreatment can prominently enhance the release of soluble substances and methane production, aiding the utilization of PDS oxidation technology for improving anaerobic bioconversion of sludge.